The Correlation of Length of Work and Mental Workload with Work Stress at University Lecturers (Indian Journal of Forensic Medicine & Toxicology, 2020)
The main role of lecturers at Tri Dharma University, namely education, research, and community service.That makes them have certain responsibilities which if it lasts a long time will cause stress. This study aimsto determine the correlation between work time and mental workload with work stress on college lecturers inSurabaya. This descriptive study was conducted on 43 active lecturers who teach at a university in Surabaya.The results of this study were analyzed to determine the lecturer’s length of work, the mental workload oflecturers with categories from NASA TLX and their correlation with work stress. The results stated that 22people had worked for more than 20 years, as many as 25 people had very high mental workloads, and 30people with mild stress. Most of the lecturers already have a lot of experience and a large number of taskdemands but are still able to deal with everything well so that work stress does not arise. The correlation valuebetween the length of work and work stress is 0.461, and the correlation value between mental workloadand work stress is 0.808. This value states there is no correlation between the length of work and mentalworkload with work stress. Recommendations are given to universities, lecturers and all those involved inefforts to maintain the atmosphere and work culture to improve comfort for all parties, such as adding greenareas in the workspace, providing remuneration for lecturers who excel, and maintaining communicationbetween lecturers.